Management of Acute Variceal Bleed by Esophageal Variceal Ligation in an Unconventional Position—An Urban-Center Insight - Jalihal, Umesh; Shivalingaiah, Prithvipriyadarshini; Bale, Abhijith (Journal of Digestive Endoscopy, 2019)
Background Acute variceal bleed is a fatal complication in patients with liver cirrhosis, and it is important to achieve hemostasis at the earliest. Endoscopic variceal ligation (EVL) is a preferred modality in controlling variceal bleed. The blood pool in esophagus and oozing of blood from varices cause hindrance for variceal ligation leading to failure of therapy. In sitting position, it is hoped that visualization of esophagus may be better. With this background, EVL of patients in sitting position was done and results were analyzed.Methods Cirrhotics presenting with hematemesis and/or melena were included in the study. Clinical and endoscopic parameters were assessed. Among them, patients having hypotension and hepatic encephalopathy were excluded. Initial endoscopic assessment was done in left lateral position. In case of obscured visualization of esophagus due to flooding, if time taken to achieve hemostasis > 5 minutes, position was changed to sitting from left lateral decubitus. Patients with isolated gastric variceal and ulcer bleed were further excluded.Results Among 78 acute bleed patients selected, 41fulfilled the inclusion criteria for the study. During endoscopy, in 20 patients, EVL was done in left lateral decubitus position with head end elevation. Twenty-one patients were shifted from conventional left lateral position to sitting posture. Study revealed that patients undergoing EVL in sitting position had better visibility aiding the procedure and no aspiration during the procedure. There was no difference in the left lateral with head raised or without it. Duration of EVL was comparable to that of nonbleeders and additional sclerotherapy was not required in any case in both the groups. Following the procedure, patients were observed for 5 days. There was no failure of therapy which was analyzed according to Baveno VI consensus. However, there was delayed complication in one case due to sepsis and metabolic acidosis causing death.Conclusion This study suggests, in acute variceal bleed cases, EVL in sitting position aids in better visibility and helps in achieving hemostasis early with least complications.
Keywords: acute variceal bleed; endoscopic variceal ligation; cirrhosis; endoscopy